Engineering two nitrogen-containing polyhedral oligomeric silsesquioxanes (N-POSSs) to enhance the fire safety of epoxy resin endowed with superior thermal stability. (June 2022) - Ye, Xinming; Feng, Yu; Tian, Panpan; Li, Zhimao; Li, Yingchun; Wang, Wensheng; Li, Jie; Qiao, Liang; Wang, Kun; Zhang, Wenchao; Pan, Ye-Tang; Yang, Rongjie
Highlights: Two nitrogen-containing polyhedral oligomeric silsesquioxanes (N-POSSs) are synthesized via one-pot method. N-POSSs endow with ultra-high thermal stability and are suitable for industrialized production. Adding 4 wt% of AP-POSS reduces the peak heat release rate of epoxy resin by 60.6%. N-POSSs apparently reduce fire hazards of the formed EP composites. The flame retardant mechanism of N-POSSs for EP is fully illustrated. Abstract: Despite remarkable advances in developing flame retardants and smoke suppressants for epoxy resin (EP), engineering nitrogen-containing polyhedral oligomeric silsesquioxane (N-POSS) to impart superior fire safety properties to EP has remained an intractable challenge. In this work, two nitrogen-containing polyhedral oligomeric silsesquioxanes (N-POSSs), namely, aminoethyl-aminopropyl-hepta-phenyl polyhedral oligomeric silsesquioxane (AEAP-POSS) and aminopropyl-hepta-phenyl polyhedral oligomeric silsesquioxane (AP-POSS), were synthesized through the "corner-capping" reaction. The molecular structures of N-POSSs were fully characterized by FTIR, 1 H NMR, 29 Si NMR and MALDI-TOF MS, and the synthesized AEAP-POSS and AP-POSS were introduced into EP to solve the shortcomings of flammability. TGA results showed that the incorporation of 4 wt% N-POSS nanoparticles distinctly improved the char residue at 800 °C, which significantly enhanced the thermal stability of the EP composites. When 4 wt% of AP-POSS was introduced into EP, reductions in the peak of heat release rate (p-HRR), fire growth index (FGI), peak of smoke production rate (p-SPR), and the peak of CO production rate (p-COP) reached to 60.6%, 70.2%, 52.3% and 60.4%, respectively. Subsequently, TG-FTIR and XPS were utilized to investigate the flame retardancy and smoke suppression mechanism. Our work presented a considerable advancement for the facile fabrication of flame retardants based on nitrogen-containing polyhedral oligomeric silsesquioxane compounds. Graphic abstract: Image, graphical abstract